Characteristics and requirements of hypertensive patients willing to use digital health tools in the Chinese community: a multicentre cross-sectional survey - Shiqun Chen; Guoli Sun; Xiaolin Cen; Jin Liu; Jianfeng Ye; Jiyan Chen; Li Lei; Yibo He; Feier Song; Wei Guo; Yan Liang; Yuying Hu; et al. (BMC, 2020)
Abstract Background Digital health tools (WeChat or mobile health apps) provide opportunities for new methods of hypertension management for hypertensive patients. However, the willingness of these patients to use social media and mobile health apps for hypertension management remains unclear. This study explored the characteristics and requirements of patients willing to use digital health (WDH) tools to manage hypertension. Methods From February to March 2018, we administered questionnaires to 1089 patients with hypertension at eight Chinese primary medical units. We assessed independent risk factors of WDH and requirement among WDH patients. Results Overall, 43% (465/1089) of participants were WDH patients, who were younger (58 ± 12 vs 61 ± 13 years) and had a greater proportion of employed individuals (31% vs 14%) and higher education levels (65% vs 52%) than the non-WDH patients (all P < 0.0001). After adjusting for other risk factors, higher education (OR: 0.52; 95% CI: 0.34-0.79), good medicine adherence (OR: 1.5; 95% CI: 1.0-2.3) and blood pressure self-monitoring (OR: 1.6; 95% CI: 1.2-2.3) remained significantly associated with WDH (all P < 0.05). WDH patients responded that digital health tools should try to provide a platform for blood pressure monitoring (42%), medication reminders (41%), hypertension knowledge (39%) and doctor-patient communication (32%). Conclusion Our survey suggested that among hypertensive patients, willingness to use digital health tools was significantly associated with education, medicine adherence and blood pressure self-monitoring. Digital health tool developers and researchers should pay particular attention to recruiting older, less educated and unemployed patients with less willingness and who are less technologically savvy and research the requirements of WDH patients (blood pressure monitoring, medication reminders, and knowledge education) in the future.